2019
DOI: 10.1088/1555-6611/ab0a65
|View full text |Cite
|
Sign up to set email alerts
|

Field-free orientation of LiH molecule induced by two-color femtosecond and terahertz laser pulses

Abstract: We theoretically study the field-free molecular orientation by the combination of a two-color femtosecond laser pulse and a time-delayed terahertz (THz) laser pulse, with LiH as the prototype molecule. It is shown that the molecular hyperpolarizability is a vital parameter in achieving molecular orientation according to the pre-excitation created by an intense twocolor femtosecond laser pulse. The relative amplitude of the two-color femtosecond pulse is discussed. In addition, the center frequency of the THz l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…This is consistent with the conclusion that a uniform population distribution of rotational states would lead to a large molecular orientation degree [60]. The molecular orientation also depends on the phase difference between two adjacent rotational states and can be further enhanced by optimizing the decreasing the reduction of orientation resulting from the offset phase [43,60]. Figure 1C shows the phase differences Δφ j,jÀ1 in the scheme (I), the Δφ j,jÀ1 changes from flatly to steeply when 0.65 Â 10 7 V/m ≤ E 01 ≤ 1.00 Â 10 7 V/m.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with the conclusion that a uniform population distribution of rotational states would lead to a large molecular orientation degree [60]. The molecular orientation also depends on the phase difference between two adjacent rotational states and can be further enhanced by optimizing the decreasing the reduction of orientation resulting from the offset phase [43,60]. Figure 1C shows the phase differences Δφ j,jÀ1 in the scheme (I), the Δφ j,jÀ1 changes from flatly to steeply when 0.65 Â 10 7 V/m ≤ E 01 ≤ 1.00 Â 10 7 V/m.…”
Section: Resultssupporting
confidence: 89%
“…Shu et al provided an important insight into the THz-laser-induced molecular orientation and achieved a large orientation degree by the interaction of a SCP with the electric-dipole moment [33]. To further optimize the molecular orientation, researchers proposed many laser field schemes including pulse train [35][36][37][38][39][40][41] and the combination of laser pulses [42][43][44][45]. The combination of two-color femtosecond and delayed terahertz laser pulses has been proven theoretically and experimentally as a versatile method to obtain a high orientation degree.…”
mentioning
confidence: 99%
“…76 Subsequent works have further improved upon this enhancement by incorporating additional pre-alignment pulses or optimizing the parameters of the pulses. 122–124 Experimental demonstrations of this hybrid scheme have demonstrated its capability to induce transient field-free orientation of OCS molecules at low temperatures around 2 K, as well as the rotational dynamics of asymmetric molecules at ambient temperatures. 74 Moreover, a recent experiment has revealed that this scheme can significantly increase the orientation of iodomethane molecules at room temperature, surpassing the levels achieved by employing pure terahertz pulses alone.…”
Section: Control Schemes and Numerical Simulationsmentioning
confidence: 99%
“…LiH as a prototype diatomic molecule in molecular reaction dynamics has attracted considerable attention, leading to widespread investigations in recent years [1][2][3][4][5][6]. The ground state structure and potential energy function of LiH have been provided [7][8][9], and dedicated efforts have been devoted to manipulate both orientation and photodissociation process [10][11][12].…”
Section: Introductionmentioning
confidence: 99%